Pengujian Black Box pada Aplikasi Penjualan Berbasis Web Menggunakan Metode Equivalence Partitioning - Teti Desyani; Endar Nirmala; Andi Lisdiarto; Hairul Ridwan; Raden Wirawan Kukuh Pambudi; Vyka Septiani (Teknik Informatika Universitas Pamulang, 2022)
In a program or software certainly has some shortcomings in terms of comfort and accuracy to the needs of users (users), such as errors in user appearance, as well as effectiveness in the use of programs. Therefore, a way is needed to be able to fix the deficiency, by testing the program before it is used to the user. And the test is one way to determine whether a software has met the needs of users and specifications or still does not meet. If there is no checking process first, it can cause data error. With these problems, of course, it will hinder the use of the application. Therefore, the validation process is very considered. An application can be said to be of quality if it has gone through the testing stage. In the above, we conducted a blackbox test using the Equivalence Partitioning method, which can be interpreted as solving or dividing a program in the form of a domain that is entered into a data class in order to get a test case. Using this method, we earned quite varied points to test web application sales. The test in question includes things such as the design of the test scenario, the determination of the data to be tested, the test trial, the range of values, the determination of program functionality, conformity with existing databases, the results of documented research, to the conclusions obtained. The conclusion of testing using this method is that this application can run properly by meeting the criteria that meet the user's needs.